Insights in the host response towards biomaterial-based scaffolds for cancer therapy - Schluck, Marjolein; Weiden, Jorieke; Verdoes, Martijn; Figdor, Carl G. (Frontiers in Bioengineering and Biotechnology, 2023)
Immunotherapeutic strategies have shown promising results in the treatment of cancer. However, not all patients respond, and treatments can have severe side-effects. Adoptive cell therapy (ACT) has shown remarkable therapeutic efficacy across different leukaemia and lymphoma types. But the treatment of solid tumours remains a challenge due to limited persistence and tumour infiltration. We believe that biomaterial-based scaffolds are promising new tools and may address several of the challenges associated with cancer vaccination and ACT. In particular, biomaterial-based scaffold implants allow for controlled delivery of activating signals and/or functional T cells at specific sites. One of the main challenges for their application forms the host response against these scaffolds, which includes unwanted myeloid cell infiltration and the formation of a fibrotic capsule around the scaffold, thereby limiting cell traffic. In this review we provide an overview of several of the biomaterial-based scaffolds designed for cancer therapy to date. We will discuss the host responses observed and we will highlight design parameters that influence this response and their potential impact on therapeutic outcome.